PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT DAN KOMISARIS INDEPENDEN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Abidatus Suroya, Naela; Darmayanti, Novi; Shoimah, Siti (Prodi Akuntansi FEB UNITOMO, 2024)
ABSTRACT This study aims to determine the effect of Institutional Ownership, Audit Committee and Independent Commissioners on the Integrity of Financial Statements, partially or simultaneously. The population of this study were all manufacturing companies in the chemical sub-sector which were listed on the Indonesia Stock Exchange (IDX), totaling 93 companies. This study used the 2018-2022 observation period, using the purposive sampling method to obtain a sample of 70. The data analysis method used in this study was a multiple linear regression test. The variables used are Institutional Ownership, Audit Committee and Independent Commissioners as independent variables, while the Integrity of Financial Statements as the dependent variable. The results of this study resulted in the finding that partially Institutional Ownership, Audit Committees, Independent Commissioners have a significant effect on the Integrity of Financial Statements. Simultaneously, institutional ownership, audit committee and independent commissioners have a significant effect on the integrity of financial statement.